Keterpakaian Koleksi Perpustakaan Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta - Imam Mahmudi; Nushrotul Hasanah Rahmawati (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study aims to determine the utilization rate of the library collection at the Faculty of Ushuluddin and Dakwah, UIN Raden Mas Said Surakarta, as a form of evaluation for collection procurement. The research was conducted using a quantitative method with a descriptive approach. Data were collected by analyzing the 2022 procurement list, which consisted of 409 borrowable collection titles. Their utilization was then verified based on circulation (borrowing) data recorded in the Online Public Access Catalogue (OPAC) from 2022 to June 2025. Data analysis was performed using percentages to determine the collection's utilization rate. The results showed that 288 titles (70%) of the collection had been utilized, while 121 titles (30%) remained unused. Based on the criteria used, the collection utilization rate falls into the high category. The most frequently used collections were generally textbooks that support academic activities, particularly in the field of research methodology, whereas popular collections tended to be underutilized. These findings indicate that the relevance of the collection to the academic needs of users significantly influences the utilization rate. The results of this study can serve as a basis for policy-making in library collection development to ensure it is more targeted and aligned with user needs.